Is Jigsaw Learning Method Effective for Supporting Islamic Religious Education Learning at School? - Harahap, Abdi Syahrial; Rustam Ependi; Muhammad Yunan Harahap; Sekar Katresna (ASIAN PUBLISHER, 2024)
Religious education is one of the important issues that needs to be discussed because it is related to the way religious education is delivered in schools that often do not promote good multicultural education, and even tend to create divisions. The application of various learning methodologies and management is required as part of the endeavor to enhance Islamic learning outcomes. Jigsaw learning and its modified forms have been utilized in educational contexts more frequently than other cooperative learning methodologies because of its potential. This type of research is literature review research or literature study. Through library research, this study used a descriptive qualitative methodology and the literature study method. The Jigsaw method or type is a cooperative learning method by which students learn in small groups of four to six people heterogeneously. Students work together in positive interdependence and are independently responsible. In this learning, students also have many opportunities to express their opinions and can improve communication skills. The initial jigsaw method's adoption was successful in raising students' involvement in Islamic religious education learning in a number of ways, as seen by the findings. Students felt more engaged and proactive in the learning process when given structured group assignments. These results should help teachers make the best decision when it comes to teaching character education, particularly when it comes to developing mutual respect.